Modal model identification of structures under unmeasured seismic excitations. - Sepe, Vincenzo (Earthquake engineering & structural dynamics.)
Techniques developed for structural identification of a structural model are typically based on information regarding the response and the forcing actions. However, in some situations it can be necessary, or simply useful, to refer only to the measured responses. In this paper we describe a technique suitable for identifying the modal model of a spatial frame in the frequency domain when the seismic input is unknown both in time contents and direction. In some previous theoretical works we established that this identification problem has a unique solution when at least three time history responses are known. Here numerical techniques are developed which allow the evaluation of the modal quantities in practice. Numerical applications are carried out on plane and spatial framed structures by using a modal model which may be complete, including all the structure's modes, or incomplete, including only the lowest modes. In most cases the obtained results are satisfactory.